2020
DOI: 10.1371/journal.pone.0230815
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-by-genotype interaction in type 2 diabetes risk and fasting glucose

Abstract: Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 74 publications
1
14
0
2
Order By: Relevance
“…Consistent with our finding, the KCNQ1-by-smoking interaction has been reported by a study in Han Chinese patients (39). Moreover, Wu et al (15) recently identified interactions between smoking status and five SNPs at or near four genes (TCF7L2, CUBN, C2orf63, and FBN1) on the risk of diabetes, in subjects of European and African ancestry. Two out of the five SNPsmoking interactions can be replicated in our TWB2 HbA 1c and diabetes analysis, at the nominal significance level of 0.05 (Supplementary Table 17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our finding, the KCNQ1-by-smoking interaction has been reported by a study in Han Chinese patients (39). Moreover, Wu et al (15) recently identified interactions between smoking status and five SNPs at or near four genes (TCF7L2, CUBN, C2orf63, and FBN1) on the risk of diabetes, in subjects of European and African ancestry. Two out of the five SNPsmoking interactions can be replicated in our TWB2 HbA 1c and diabetes analysis, at the nominal significance level of 0.05 (Supplementary Table 17).…”
Section: Discussionsupporting
confidence: 92%
“…Smoking is coded as 1 for active smokers and 0 otherwise. Sex, age, BMI, educational attainment, and ancestry PCs are commonly adjusted in models for FG, HbA 1c , and diabetes (14,15). Regular physical exercise has been shown to reduce the risk of insulin resistance, metabolic syndrome, and diabetes (16).…”
Section: Definition Of Smoking Drinking Regular Exercise and Educational Attainmentmentioning
confidence: 99%
“…A genome-environment-wide-interaction study suggested possible mechanisms that link T2D to cigarette smoking. 11 …”
Section: Introductionmentioning
confidence: 99%
“…problemas micro ou macrovasculares (MAGLIANO et al, 2020). As mudanças no estilo de vida é um ponto que deve ser destacado, especialmente em curto período de tempo (CARE DIABETES, 2019;WU et al, 2020). No Brasil, um estudo realizado na comunidade de origem japonesa mostrou acentuado aumento da prevalência de diabetes, cuja porcentagem passou de 18,3% em 1993, para 34,0% em 2000, evidenciando que o impacto produzido pelas alterações no modo de vida, em particular no padrão alimentar e no nível de atividade física, em uma população com provável suscetibilidade genética, podem ser cruciais para desenvolver o DM2 (SBD, 2017).…”
unclassified
“…Internacional Journal of Biological Macromolecules(JUTTADA et al, 2020), que revela o risco de desenvolver diabetes tipo 2 foi conferido pelo SNP rs7903146 do gene do fator de transcrição 7-like2 em muitas populações étnicas, visto que é uma característica não mutável, é importante tentar evitar os demais fatores de risco.Contudo, a presença de Síndrome Metabólica, de modo geral, manifesta-se como conjunto de sinais que reforçam as complicações clinicas de quem tem altas chances de desenvolver diabetes, somando a isso, estes mesmos acadêmicos com SM, também possuem comportamento peculiar, como o tabagismo, ver na Tabela 4, ao passo que corrobora para o aparecimento de outras comorbidades consecutivamente associadas a hiperglicemia, podendo agregar problemas ainda mais graves de ordem vascular, tal qual: o acidente vascular cerebral, infarto agudo do miocárdio e trombose venosa profunda(WU et al, 2020).Diante dos resultados detectados, levando em consideração o ferramental proposto, pode-se perceber que apesar das limitações da metodologia, o estilo de vida, obesidade e a circunferência abdominal são os principais vilões da elevação dos escores para os grupos com mais riscos para DM2, especialmente no sexo masculino, porém existe a necessidade de estudos prospectivos afim de pesquisar se esses fatores estão sendo adquiridos ao longo da graduação. Além do mais, a presença de síndrome metabólica reforça o contexto de que até Rastreamento de fatores de risco para diabetes tipo 2 em acadêmicos de medicina mesmo as populações mais jovens já estão susceptíveis ao DM2, isso impacta negativamente, gerando enormes custos emocionais e financeiros à sociedade.…”
unclassified